Analysis of the Application of STEM Approaches in Mathematics Learning in Junior High Schools - Mubarik, Mubarik; Permata, Dyah; Pathuddin, Pathuddin; Anggraini, Anggraini; Nasir, Rahma; Alfisyahra, Alfisyahra; Meinarni, Welli; Fajriani, Fajriani; Desti, Desti; Rumi, Moh. Fadhel; Ulfiana, Dewi; Muazin, Muhammad (Universitas Sembilanbelas November Kolaka, 2022)
The integration of ICT in learning is a component of 21st-century learning. Science and technology always develop rapidly from time to time. Â The purpose of this study is to determine the knowledge and abilities of junior high school mathematics teachers in STEM learning. This research was also conducted to determine student knowledge related to STEM learning. This study used a mixed method. The results showed that most junior high school mathematics teachers in the Donggala district did not understand STEM/STEAM learning. The teacher has also not been able to apply the STEM/STEAM approach in the learning process. Therefore, it is hoped that mathematics teachers in the Donggala district can apply a STEAM-based approach combined with local wisdom in the Donggala district. And it is necessary to conduct training to improve teacher competencies related to STEM learning.